Mechanisms underlying cognitive impairment in a mouse model of familial hypercholesterolemia: Evidences of LDLr ‐/‐ mice. (December 2021) - Rodrigues, Matheus Scarpatto; de Oliveira, Jade; Engel, Daiane F; de Paula, Gabriela C; Melo, Helen M; Lopes, Samantha C; Ribeiro, Camila T; Machado, Alessandra Gonçalves; Bast, Rachel KSS; Moreira, José Claudio F; Gelain, Daniel P; Prediger, Rui D; et al.
Abstract: Background: Familial hypercholesterolemia (FH) is a genetic disorder caused by low‐density lipoprotein receptor (LDLr) dysfunction, resulting in elevated plasma cholesterol levels. Previous reports have shown an interplay between LDLr and amyloid‐β (Aβ) metabolism, a peptide linked to Alzheimer's disease. Indeed, LDLr‐/‐ mice are more vulnerable to the deleterious memory impact induced by Aβ. Here, we investigated whether the gene expression of proteins involved in Aβ metabolism and Aβ content is altered in adult or middle‐aged LDLr‐/‐ mice brains. Also, we investigated neuroinflammation as well as neuronal and synaptic damage. Method: Young adult (3‐month‐old) and middle‐aged (14‐month‐old) male C57BL/6 wild‐type (WT) and LDLr‐/‐ mice were first submitted to the Morris water maze test. After spatial memory assessment, the Aβ1‐42 levels and gene expression of proteins involved in Aβ synthesis were evaluated in the prefrontal cortex (PFC) and hippocampus of 3 and 14‐months‐old WT and LDLr‐/‐ mice. We also assessed the apoptosis signaling, levels of synaptic proteins, and Iba‐1 immunoreactivity (a marker for microglia) in the experimental groups' brain structures. Result: LDLr‐/‐ mice presented spatial memory impairment, which was more severe in middle‐aged animals, which was not associated with altered expression of proteins involved in Aβ processing and Aβ1‐42 levels in either hippocampus or PFC. We further found that the expression of the apoptotic protein Bax was increased in both the PFC and hippocampus of 3‐ and 14‐month‐old LDLr‐/‐ mice. LDLr‐/‐ mice presented increased immunoreactivity for activated caspase‐3 in the neurons of the PFC and hippocampus. We also observed a reduction in immunocontent of PSD 95 in the hippocampus of 3‐month‐old LDLr‐/‐ mice. Moreover, synaptophysin immunocontent was decreased in the middle‐age LDLr‐/‐ mice hippocampi. In addition, we observed that LDLr‐/‐ mice displayed increased immunoreactivity for Iba‐1 in the PFC already at 3 months of age and in the hippocampus at middle‐age. Finally, we found that LDLr ‐/‐ at middle‐age exhibited microglial morphological changes related to their activated state in the PFC. Conclusion: Cognitive impairments in LDLr‐/‐ mice were associated with exacerbation of neuronal apoptosis, synaptic dysfunction, and microglial activation in brain regions related to memory formation, but not with significant changes in Aβ processing or levels.